Conservation Demand of Asystasia dalzelliana (Acanthaceae) â€“ An Endemic Medicinal Herb Of Southern Western Ghats - KUMAR, ANIL V S; LEKSHMI, DEEPA V S (Indian Forester, 2023)
Distributional status of the endemic herb Asystasia dalzelliana has been recorded from Kerala.Â  Unlike other species of the genus which show bulk populations and often recognized as noxious weeds, A.dalzelliana exhibits low populations. Exploitation for medicinal purpose and habitat destruction has been considered as the probable causes. Survey has been carried out across 8 districts of Kerala and only limited populations could be observed in the natural habitats and further, the number of plants per population was also highly restricted. The species warrants urgent conservation measures.